Genjek Art: A Gender Ideological Battle Arena (A Perspective from Pierre Bourdieu's Capital Theory) - Luh Putu Sendratari; I Ketut Margi; Lola Utama Sitompul; Fitri Noviani; Santana Sembiring (Jurnal Ilmiah Ilmu Sosial, 2026)
Art observers note that there is still insufficient research into the turmoil and ideological clashes within the arts. This article aims to emphasize that the realm of art is open to analysis from various perspectives, including genjek. This art form falls under the category of folk art and historically emerged from the encouragement of farmers to express their artistic passions in their spare time. Buleleng has a strong tradition of genjek art in its rural areas, which has since evolved alongside the development of tourism in the region. Genjek serves as a form of cultural capital, evident in the artistic performances, pronunciation, and linguistic style of the songs produced. Through these artistic expressions and the widespread promotion of genjek art, cultural reproduction occurs, which can shape power dynamics and potentially lead to violence from a gender perspective. Additionally, the conflict between gender ideology and feminist ideology is apparent through the use of hidden transcripts in genjek performances. In this sense, genjek art not only serves entertainment purposes but also needs to be developed as an educational tool. Furthermore, genjek art contains economic potential that can serve as a foundation for entrepreneurship in the performing arts sector.